1979
DOI: 10.1007/bf01005033
|View full text |Cite
|
Sign up to set email alerts
|

The use of proteolytic enzymes to improve immunoglobulin staining by the PAP technique

Abstract: Proteolytic enzymes, protease and trypsin have recently been introduced to reduce the inconsistency hitherto encountered in the unlabelled antibody--enzyme method using PAP. This study investigated factors determining the optimum conditions for use of such enzymes in order to establish which one is most suitable. Trypsin was the most effective enzyme; however, its activity decreased over 3 h, a feature paralleled immunocytochemically. Method and duration of fixation appears to influence the required time of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(58 citation statements)
references
References 5 publications
1
57
0
Order By: Relevance
“…Treatment of sections with trypsin (Curran & Gregory, 1978;Mepham et al, 1979) was found to be necessary to achieve maximal staining for all three proteins. In non-trypsinized sections staining for fibronectin was weak except in the smooth muscle underlying the submucosa (Figure la, c), and there was essentially no staining for laminin (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of sections with trypsin (Curran & Gregory, 1978;Mepham et al, 1979) was found to be necessary to achieve maximal staining for all three proteins. In non-trypsinized sections staining for fibronectin was weak except in the smooth muscle underlying the submucosa (Figure la, c), and there was essentially no staining for laminin (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…Among these, FA treatment is the standard method mainly used for Aβ IHC of FFPE brain tissue sections, although it was originally developed for the immunoreactive enhancement of cerebral amyloids (prion protein and Aβ) and systemic amyloids (amyloid A and prealbumin) (Kitamoto et al 1987). The pretreatment of protein digestion with an enzyme such as trypsin had been used for IHC but only in a limited application (Battifora and Kopinski 1986;Huang et al 1976;Mepham et al 1979). In 1991, the advent of the heating AR method was a breakthrough in the field of IHC.…”
Section: Discussionmentioning
confidence: 99%
“…Between the absolute and 95% ethanol washes, samples were incubated for 10 min in a 0.3% H 2 O 2 (v/v) methanol solution to quench endogenous peroxidase activity. Antigen retrieval methods employing enzymatic digestion (0.05-0.25% trypsin; 0.1% pepsin at 37C) and microwave/steamer heating (10 mM citrate buffer, pH 6.0) were tested to optimize SCCA1 and SCCA2 immunostaining (Mepham et al 1979;Shi et al 1993). A 10-min incubation with 1 ϫ trypsin-EDTA (0.05% trypsin, 0.53 mM EDTA.4Na; Gibco BRL, Grand Island, NY) at 37C enhanced SCCA2 staining, whereas neither procedure improved SCCA1 staining.…”
Section: Immunohistochemistrymentioning
confidence: 99%